HUBUNGAN VARIASI IKLIM DENGAN KEJADIAN PNEUMONIA PADA BALITA DI KOTA SEMARANG TAHUN 2011-2015 (STUDI KASUS DI WILAYAH KERJA PUSKESMAS BANDARHARJO) - Rismawati Rismawati; Budiyono Budiyono; Suhartono Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Climate change affects human health through increased frequency of respiratory and cardiovascular diseases, especially pneumonia in children. The climatic conditions in the city of Semarang has increased an average temperature of 0.1°C and humidity is on average 1.6% annually. Pneumonia remains a major problem in Semarang, especially in Puskesmas Bandarharjo. Trendline shows the number of pneumonia cases continue to rise to 430 cases in 2015. The study shows that one of the risk factors for pneumonia are the climatic conditions. The purpose of this study was to analyzed the relationship of climate variation with the incidence of pneumonia toddler in Semarang 2011-2015. This research is descriptive analytic with cross sectional approach. Methods of data analysis using Rank Spearman. Secondary data were taken from reports cases of pneumonia in Puskesmas Bandarharjo toddler period 2011-2015. Climate data include air temperature, air humidity and rainfall in the period 2011-2015 is taken from BMKG Semarang. The results showed that during the period 2011-2015 the average temperature was 28.14 ° C, the highest average 28.27 ° C occurred in 2015 and the lowest was 28.05 ° C in 2012. While the average humidity is 76.13%, the highest average 77.16% in 2013 and the lowest was 74.83% in 2015 and an average rainfall of 180.26 mm / month with an average high of 202.58 mm / month in the year 2013, and an average low of 125.66 mm / month in 2015. the result of the correlation between the incidence of infant pneumonia in Puskesmas Bandarharjo with air temperature (p value = 0.492; r = 0.09), relative humidity (p value = 0.234; r = -0.156) and precipitation (p value = 0.088; r = -0.222). The conclusion of this study is the factor of climate variation was not associated with the incidence of pneumonia in infants in Puskesmas Bandarharjo.